2013
DOI: 10.1016/j.hrthm.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Apamin induces early afterdepolarizations and torsades de pointes ventricular arrhythmia from failing rabbit ventricles exhibiting secondary rises in intracellular calcium

Abstract: Background A secondary rise of intracellular Ca2+ (Cai) and an upregulation of IKAS are characteristic findings of failing ventricular myocytes. We hypothesize that apamin, a specific IKAS blocker, may induce torsades de pointes (TdP) ventricular arrhythmia from failing ventricles exhibiting secondary rises of Cai. Objectives To test the hypothesis that small conductance Ca2+ activated apamin sensitive K+ current (IKAS) maintains repolarization reserve and prevents ventricular arrhythmia in a rabbit model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 28 publications
3
76
0
Order By: Relevance
“…Apamin induced very little change of APD 80 in VMs at PCLs between 500 and 1000 ms. APD 80 prolongation was observed with 2000 and 4000 ms PCLs. The latter finding is consistent with a previous study which showed that apamin increased APD 80 of Langendorff‐perfused normal rabbit ventricles only when the PCL was ≥800 ms 21. For all cells studied, apamin prolonged APD 80 of PCs (n=9) from 228±12 to 244±17 ms (6.63% increase) at 2000 ms PCL, from 203±18 to 226±3 ms (9.22% increase) at 1000 ms PCL, from 190±26 to 199±16 ms (5.58% increase) at 600 ms PCL and from 171±16 to 177±25 ms (2.2% increase) at 500 ms PCL.…”
Section: Resultssupporting
confidence: 93%
“…Apamin induced very little change of APD 80 in VMs at PCLs between 500 and 1000 ms. APD 80 prolongation was observed with 2000 and 4000 ms PCLs. The latter finding is consistent with a previous study which showed that apamin increased APD 80 of Langendorff‐perfused normal rabbit ventricles only when the PCL was ≥800 ms 21. For all cells studied, apamin prolonged APD 80 of PCs (n=9) from 228±12 to 244±17 ms (6.63% increase) at 2000 ms PCL, from 203±18 to 226±3 ms (9.22% increase) at 1000 ms PCL, from 190±26 to 199±16 ms (5.58% increase) at 600 ms PCL and from 171±16 to 177±25 ms (2.2% increase) at 500 ms PCL.…”
Section: Resultssupporting
confidence: 93%
“…Subsequent investigations showed that the apamin-sensitive potassium current ( I KAS ) is present in the atria [5][12]. In addition, while normal ventricles paced at physiological cycle lengths do not express significant I KAS [13], we and others found that I KAS expression is upregulated in failing, ischemic or infarcted human, rabbit and rat ventricles and in normal rabbit ventricles with complete atrioventricular block [14][19]. A common criticism of all these studies is that the specificity of apamin in cardiac type ion channels has not been well established.…”
Section: Introductionmentioning
confidence: 62%
“…It is envisioned that the electrophysiological changes resulting from K ϩ channel down-regulation promote the development of "atrial torsade de pointes" for AF initiation. Indeed, a recent report showed that apamin induces early after-depolarizations and torsade de pointes in failing rabbit ventricles, confirming that suppression of SK channels is proarrhythmic (32).…”
Section: Down-regulation Of Sk Channels In Diabetesmentioning
confidence: 76%